Using 3dRNA for RNA 3‐D Structure Prediction and Evaluation. Issue 1 (2nd May 2017) - Wang, Jian; Xiao, Yi
Abstract: This unit describes how to use 3dRNA to predict RNA 3‐D structures from their sequences and secondary (2‐D) structures, and how to use 3dRNAscore to evaluate the predicted structures. The predicted RNA 3‐D structures can be used to predict or understand their functions and can also be used to find the interactions between the RNA and other molecules. © 2017 by John Wiley & Sons, Inc.